2016
DOI: 10.4274/jcrpe.2504
|View full text |Cite
|
Sign up to set email alerts
|

Lower Plasma Ghrelin Levels are Found in Women with Diabetes-Complicated Pregnancies

Abstract: Objective:To evaluate the associations of glycemic control and gestational age with ghrelin and proinsulin levels in cord blood and mothers’ peripheral blood during pregnancy.Methods:This is a cross-sectional comparative study of twenty-four pregnant women with gestational diabetes (GD), 18 with type 2 diabetes mellitus (T2DM), and 36 without diabetes, as well as their neonates. Levels of proinsulin, ghrelin, and glycated hemoglobin A1c (HbA1c) were measured from maternal blood during the last week before caes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Diabetic pregnancy may involve a positive or negative caloric balance. Circulating ghrelin decreases during physiological pregnancy, which represents a natural insulin-resistant state [ 8 , 33 ]. However, gestational glucose-induced ghrelin suppression is preserved at a lower level, and is probably not related to the degree of insulin resistance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diabetic pregnancy may involve a positive or negative caloric balance. Circulating ghrelin decreases during physiological pregnancy, which represents a natural insulin-resistant state [ 8 , 33 ]. However, gestational glucose-induced ghrelin suppression is preserved at a lower level, and is probably not related to the degree of insulin resistance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gómez-Díaz et al [ 8 ] observed that pregnant women with GDM and T2DM had significantly lower serum ghrelin levels compared with non-diabetic patients. This statistical difference can be connected to the fact that approximately half of the patients were receiving insulin in the study of Gómez-Díaz et al [ 8 ], who in fact admitted that this treatment heterogeneity might have been a confounding factor. Meanwhile, all of the women with GDM in our study were treated with insulin during pregnancy until delivery, yet the serum and urine samples were taken 48 h after delivery, which means at least 48 h without gestational treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentrations were lower in pregnant women with diabetes and HbA1c of < 6.5%. It has been suggested that ghrelin is involved in the adaptation to the caloric imbalance in GDM patients and may play a similar role in pregnancy-related complications, since high ghrelin concentrations may be vital for normal fetal development [28]. Riedl et al have observed that whereas basal ghrelin concentrations are suppressed during pregnancy, the downregulation of ghrelin by glucose uptake is markedly reduced [29].…”
Section: Ghrelinmentioning
confidence: 99%